Academic Honesty in the International Baccalaureate Diploma Programme: Student, Teacher, and School Perspectives - Burbidge, Tamsin; Hamer, Rebecca (Journal of International Students, 2020)
Much of the existing research on academic integrity surveys students. This study compares survey responses of students, teachers, and school administrators from schools in 76 countries worldwide. The surveys addressed their knowledge, understanding, and attitudes toward academic honesty, how it is taught at their school, as well as school experiences. Results indicate that students mostly learn about academic integrity in the classroom. Most schools have a process to ensure students know about academic honesty, but half of schools indicate there is no similar process for teachers. State schools rely significantly more on student and teacher initiative to refresh or check their knowledge, such as accessing handbooks, and less on offering targeted student or teacher academic integrity training, than private schools.